2014
DOI: 10.15567/mljekarstvo.2014.0305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood serum selenium on udder health in dairy cows

Abstract: The aim of this study was to determine the effect of selenium concentration in early lactation on mammary gland health and histological characteristics of the udder. The experiment included 30 high-yielding Holstein-Friesian cows. Selenium concentrations in blood and milk serum, and the average somatic cell count in the first and sixth months of lactation were analyzed. After exclusion of the experimental cows from the herd, histological characteristics of the udder were examined (the degree of leukocyte infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…This finding correlated with other research that indicated peak selenium concentration in blood and serum 5 h post intramuscular injection of selenium that lasted for 28 days (Arthington et al 2014). No significant differences in average serum selenium values post injection with Se-methionine were indicated in this trial, which was similar to findings of Pechova et al (2008) and Davidov et al (2014). However, these findings differ from those of Prased and Aora (1991) that indicated an increase in blood selenium levels following orally supplemented Se-methionine.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding correlated with other research that indicated peak selenium concentration in blood and serum 5 h post intramuscular injection of selenium that lasted for 28 days (Arthington et al 2014). No significant differences in average serum selenium values post injection with Se-methionine were indicated in this trial, which was similar to findings of Pechova et al (2008) and Davidov et al (2014). However, these findings differ from those of Prased and Aora (1991) that indicated an increase in blood selenium levels following orally supplemented Se-methionine.…”
Section: Discussionsupporting
confidence: 92%
“…The injection of Na-selenite also led to a negative correlation between average milk selenium concentration and average SCC over the 60-day trial period. This finding corresponds with literature stating that bulk tank milk selenium concentration responds rapidly to changes in selenium intake (Ceballos-Marques et al 2012; Davidov et al 2014), but the results do not correlate with research done by Alejandro et al (2012), which indicated that there was no relationship between bulk tank selenium concentrations and SCC. The untreated control cows showed a constant percentage increase in average SCC compared with the groups of cows that were injected with Na-selenite for the duration of the trial.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[ 82 ] found that the repeated parenteral administration of a product containing Vitamin E and Se to pregnant dairy cows showed a positive effect on the immune response, increasing the concentrations of alpha-tocopherol and Se in plasma and colostrum, as well as a reduction of clinical forms of mastitis post-calving. Selenium-deficient cows had greater SCC, exhibited inflammatory processes in the udder (stronger immune infiltration of parenchymal cells), inflammation in the parenchyma of the mammary gland (acinar atrophy, connective tissue proliferation, and granuloma formation) [ 83 ]. When included selenium in the diet, the prevalence of intramammary infection and SCC decreases [ 84 - 86 ].…”
Section: Resultsmentioning
confidence: 99%